Compressible, anti-fatigue, extreme environment adaptable, and biocompatible supramolecular organohydrogel enabled by lignosulfonate triggered noncovalent network - Yihui Gu; Chao Xu; Yilin Wang; Jing Luo; Dongsheng Shi; Wenjuan Wu; Lu Chen; Yongcan Jin; Bo Jiang; Chaoji Chen (Nature Communications)
Abstract Achieving a synergy of biocompatibility and extreme environmental adaptability with excellent mechanical property remains challenging in the development of synthetic materials. Herein, a “bottom-up” solution-interface-induced self-assembly strategy is adopted to develop a compressible, anti-fatigue, extreme environment adaptable, biocompatible, and recyclable organohydrogel composed of chitosan-lignosulfonate-gelatin by constructing noncovalent bonded conjoined network. The ethylene glycol/water solvent induced lignosulfonate nanoparticles function as bridge in chitosan/gelation network, forming multiple interfacial interactions that can effectively dissipate energy. The organohydrogel exhibits high compressive strength (54 MPa) and toughness (3.54 MJ/m3), 100 and 70 times higher than those of pure chitosan/gelatin hydrogel, meanwhile, excellent self-recovery and fatigue resistance properties. Even when subjected to severe compression up to a strain of 0.5 for 500,000 cycles, the organohydrogel still remains intact. This organohydrogel also demonstrates notable biocompatibility both in vivo and vitro, environment adaptability at low temperature, as well as recyclability. Such all natural organohydrogel provides a promising route towards the development of high-performance load-bearing materials.